Cuticle hydrocarbons in saline aquatic beetles - María Botella-Cruz; Adrián Villastrigo; Susana Pallarés; Elena López-Gallego; Andrés Millán; Josefa Velasco (PeerJ, 2017)
Hydrocarbons are the principal component of insect cuticle and play an important role in maintaining water balance. Cuticular impermeability could be an adaptative response to salinity and desiccation in aquatic insects; however, cuticular hydrocarbons have been poorly explored in this group and there are no previous data on saline species. We characterized cuticular hydrocarbons of adults and larvae of two saline aquatic beetles, namely Nebrioporus baeticus (Dytiscidae) and Enochrus jesusarribasi (Hydrophilidae), using a gas chromatograph coupled to a mass spectrometer. The CHC profile of adults of both species, characterized by a high abundance of branched alkanes and low of unsaturated alkenes, seems to be more similar to that of some terrestrial beetles (e.g., desert Tenebrionidae) compared with other aquatic Coleoptera (freshwater Dytiscidae). Adults of E. jesusarribasi had longer chain compounds than N. baeticus, in agreement with their higher resistance to salinity and desiccation. The more permeable cuticle of larvae was characterized by a lower diversity in compounds, shorter carbon chain length and a higher proportion of unsaturated hydrocarbons compared with that of the adults. These results suggest that osmotic stress on aquatic insects could exert a selection pressure on CHC profile similar to aridity in terrestrial species.